ANALISIS KINERJA PAJAK HOTEL DI KOTA PALU - Rismawati, Andi (Fakultas Ekonomi Universitas Tadulako, 2016)
The purpose of this study is to determine the performance of hotel tax in Palu using value for money approach consisting of three ratios that are: economic ratio, ratio efficiency and effectiveness ratio. Data collection technique includes field research, literature research, and interview. The results of this study show that economic ratio of hotel tax in Palu City in 2013-2016 is considered more